Tata Kelola Kearsipan Mobile Dengan Sistem Pencatatan Surat Perintah Tugas dan Surat Perjalanan Dinas Berbasis Web (Studi Kasus Dinas Ketahanan Pangan Provinsi Kalimantan Tengah): Mobile Archival Governance with a Web-Based Recording System for Assignment and Business Travel Orders (Case Study at the Food Security Office of Central Kalimantan Province - Amanda V.R., Joseph; Sam'ani; Ichsan, Yakub; Candra, Christian Adi; Ichsan, Delon; Yudha R., Muhammad; Wedasmara, I Kadek Deo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The advancement of information technology has encouraged government institutions to shift from manual recording systems to more efficient and integrated digital systems. The Food Security Office of Central Kalimantan Province still records Assignment Orders (SPT) and Business Travel Orders (SPPD) conventionally using logbooks. This process is time-consuming, prone to recording errors, and complicates the retrieval of documented data. Based on these problems, this study aims to design and develop a web-based recording system for SPT and SPPD that can improve efficiency, accuracy, and facilitate data management. The research method employed is Research and Development (R&D), which includes the stages of problem identification, data collection through observation and interviews, system design using flowcharts, use case diagrams, and user interface design, system development with PHP, MySQL, and XAMPP, followed by testing and evaluation. The results indicate that the system successfully replaces manual recording and provides core features such as login, data entry, data viewing, and data searching, supported by automatic numbering. System testing conducted with employees demonstrated improved recording speed and easier access to data.